Anisotropic creep fracture mechanism and microstructural evolution in nickel-based single crystal specimen with a center film hole. (August 2020) - Zhang, Dongxu; He, Jinyang; Liang, Jianwei
Highlights: The anisotropic creep fracture mechanism and microstructural evolution around a film hole were studied. A modified damage model was used to simulate the deformation behavior. The relationship between the microstructural evolution and local stress state around the film hole was found. The results of FEA agreed with both the test results and fracture morphology. Abstract: The influence of orientation on the creep rupture properties of nickel-based single crystal superalloy with a center film hole was carried out at 980 °C and 300 MPa. The mechanisms of creep rupture and microstructural evolution of the specimens were studied through macro- and micro-morphological observations and finite element analysis. The central film hole exhibited the creep-strengthening effect on the nickel-based single crystal plate specimens. The degree of strengthening was related to crystal orientations, and the most prominent effect was observed in the [0 1 1] orientation. The steady-state creep rate of the specimens with central film holes decreased in the order of [0 0 1] > [0 1 1] > [1 1 1], which was completely opposite of the specimens without central holes. The creep rupture mechanism occurred due to the growth and aggregation of micro-cracks and voids. The microstructural evolution in the strengthening phase γ' of the specimens with central film holes was closely related to the local stress state. In the high-stress zone where fractures originated, the rafting directions of the [0 1 1] and [1 1 1] orientations formed a 50° angle with the loading axis, and that of the [0 0 1] orientation was perpendicular to the loading axis. The modified crystal plastic-damage model was employed to perform the analysis of stress and damage around the center hole. The simulation results concorded well with the experimentally observed fracture behaviors.